2014
DOI: 10.1107/s1600576714004476
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic study of grain refinement of Al by Nb addition

Abstract: The grain refinement of Al by the addition of a small amount of peritecticforming solute, Nb, has been studied from the crystallographic point of view. Combining the observations of optical microscopy and scanning electron microscopy with the results of energy-dispersive X-ray spectroscopy and X-ray diffraction, it is confirmed that the particles observed at or near the grain centres of refined Al alloys are pro-peritectic Al 3 Nb particles. The crystallographic matching between the Al 3 Nb particles and Al gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 46 publications
(57 reference statements)
3
22
1
Order By: Relevance
“…[8][9][10][11] Recent studies have reported that the niobium addition which forms Al 3 Nb particles in the melt is found to be an effective grain refiner of Al-Si alloys. [12][13][14][15] Further, it has been observed that the addition of Nb along with B enhances the grain refinement of Al-Si alloys as compared to the refinement occurring with only Nb or boron additions. This enhanced grain refinement was attributed to the similarities between the Al-Nb-B and Al-Ti-B systems.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Recent studies have reported that the niobium addition which forms Al 3 Nb particles in the melt is found to be an effective grain refiner of Al-Si alloys. [12][13][14][15] Further, it has been observed that the addition of Nb along with B enhances the grain refinement of Al-Si alloys as compared to the refinement occurring with only Nb or boron additions. This enhanced grain refinement was attributed to the similarities between the Al-Nb-B and Al-Ti-B systems.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the solidification of antimony, silver and copper alloys, Asato and co-workers firstly defined the conceptual peritectic reaction theory [156]. Then, it was introduced to elucidate the grain refinement of aluminium alloys by Al 3 Ti (Crossley and Mondolfo [145]) and Al 3 Zr/Al 3 Nb (Wang et al [162,163]), respectively. Similarly, Emley [146] also used peritectics to explain the grain refinement of Mg-Zr alloys.…”
Section: Interdependence Theorymentioning
confidence: 99%
“…Then, the convergent beam Kikuchi line diffraction pattern (CBKLDP) technique [216] was introduced to determine the ORs between the nucleant particles and surrounding Zn grains. The CBKLDP technique has been proven to be an accurate and reliable method for ORs' determination [162,163,218,219]. To determine the ORs using CBKLDP technique, six steps should be conducted as follows:…”
Section: Determination Of Ors Using Cbkldp Techniquementioning
confidence: 99%
See 2 more Smart Citations